The antihypertensive efficacy of a quadruple single-pill combination in patients with resistant hypertension: study protocol for a randomized, open-label, crossover trial - Yuanyuan Yao; Xin Zhang; Runyu Ye; Shanshan Jia; Xiangyu Yang; Xiaoping Chen (Trials)
Abstract Background Resistant hypertension (RH) is defined as uncontrolled blood pressure (BP) despite treatment with at least three or more antihypertensive agents. Compelling evidence has shown that such a population has a greater risk of cardiovascular events as well as mortality. Although mineralocorticoid receptor antagonists (MRAs) have been shown to be an effective fourth-line treatment for RH, a significant proportion of RH patients do not achieve their blood pressure target. Compound reserpine and triamterene tablets, a traditional Chinese quadruple single-pill combination, have been proven to have good antihypertensive effects as well as safety, and are promising effective antihypertensive drugs for treating RH. Methods A randomized crossover clinical trial will be conducted to compare the efficacy and safety of compound reserpine and triamterene tablets treatment regimen (two tablets of olmesartan/amlodipine (OA) + one tablet of compound reserpine and triamterene tablets) with those of a standard treatment regimen (two tablets of OA + indapamide 2.5 mg + spironolactone 20 mg) in patients with RH. Forty patients will be recruited and randomly assigned in a 1:1 ratio to 2 crossover groups. The two groups will receive different combination therapies for 6 weeks and will then switch to the other combination therapy for 6 weeks, with a 4-week wash-out. The primary outcome will be the reduction in average 24-h systolic blood pressure after 6 weeks of intervention between the two groups. Discussion This study aimed to evaluate whether the compound reserpine and triamterene tablets treatment regimen (A + C + 0) results in a greater reduction in blood pressure in RH patients than the standard treatment regimen (A + C + D + spironolactone). Trial registration Chinese Clinical Trial Registry ChiCTR2400081878. Registered on March 14, 2024 ( http://www.chictr.org.cn ).